FACTORS THAT INFLUENCE STUDENT TEAMS IN INFORMATION SYSTEM DEVELOPMENT PROJECT: STUDENT’S PERSPECTIVES - Sofiyanti Indriasari; Dana Indra Sensuse (Jurnal Sistem Informasi, 2014)
The success of information systems development activities are influenced by technology and human resources. Experience and knowledge of team members is the key to performance improvements in the software development process. So the experience and knowledge are considered to be one of the main capitals in the success of a software development team. However, what if the information system development team are students who may not have experience at all ? Is the information system developed by an un-experienced team always fail ? Therefore, it is necessary to conduct a study to identify the factors that influence the student teams in information systems development project. The study was conducted with the literature study to establish research model. Furthermore, a survey conducted by distributing questionnaires to students of information systems whom are doing an internship in developing information systems. The results of the survey were analyzed quantitatively using Partial Least Square technique to test the proposed research model. The results of this study indicate that the development of information systems conducted by a team of students is significantly influenced by the Customer Relationship and Horizontal Relationship. Capability factor have a significant effect although the effect is small on the student teams.